2009
DOI: 10.1051/0004-6361:200810803
|View full text |Cite
|
Sign up to set email alerts
|

Models of turbulent dissipation regions in the diffuse interstellar medium

Abstract: Aims. Supersonic turbulence is a large reservoir of suprathermal energy in the interstellar medium. Its dissipation, because it is intermittent in space and time, can deeply modify the chemistry of the gas. This is clearly seen in the framework of shock chemistry. Intense turbulent dissipation also occurs in regions of large velocity shears, sharing with shocks the property of intermittency. Whether these bursts of dissipation, short-lived and localized, have a measurable impact on molecular abundances in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
201
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(214 citation statements)
references
References 90 publications
11
201
1
1
Order By: Relevance
“…In this letter, we present the first detection of SH absorption features in the near-UV in translucent interstellar clouds. The results presented here are well consistent with the predictions of SH production from the models for turbulent dissipation regions (TDRs) and C-type shocks that were recently introduced by Godard et al (2009Godard et al ( , 2014, Lesaffre et al (2013), Neufeld et al (2015).…”
Section: Introductionsupporting
confidence: 88%
“…In this letter, we present the first detection of SH absorption features in the near-UV in translucent interstellar clouds. The results presented here are well consistent with the predictions of SH production from the models for turbulent dissipation regions (TDRs) and C-type shocks that were recently introduced by Godard et al (2009Godard et al ( , 2014, Lesaffre et al (2013), Neufeld et al (2015).…”
Section: Introductionsupporting
confidence: 88%
“…Tielens et al (1993) have investigated that shocks do not contribute to the chemistry of the Orion Bar; therefore, we consider this scenario unlikely. Another scenario for CH + formation that has been successful in reproducing CH + abundances for the diffuse interstellar medium is the dissipation of turbulence (Godard et al 2009(Godard et al , 2012. Though the CH + 1-0 and 2−1 transitions have broader line widths than most dense gas tracers in the Orion Bar, most of the lines detected in the Orion Bar are narrow (2-3 km s −1 ); therefore, we find it unlikely that turbulence plays a role in the chemistry of species detected in the Orion Bar.…”
Section: Discussionmentioning
confidence: 99%
“…For low-density diffuse interstellar clouds, C-shocks (Pineau des Forêts et al 1986) and turbulent dissipation (Godard et al 2009) have been proposed and confirmed by Falgarone et al (2010a,b) and Godard et al (2012). Alternatively, in denser regions with strong far-ultraviolet (FUV) radiation fields, the internal energy available in the vibrationally excited H 2 molecules A&A 550, A96 (2013) has been proposed to help overcome the large activation barrier (Sternberg & Dalgarno 1995;Agundez et al 2010).…”
Section: Introductionmentioning
confidence: 86%
“…These pure velocity-structures do not follow those of dense gas: they tend to be parallel to the magnetic field orientation, they are associated with gas warmer (T kin > 25 K) than the bulk of the gas, and they bear chemical signatures of a warm chemistry that is not driven by UV photons (Falgarone et al 2006;Godard et al 2009). In one of these E-CVI structures, Plateau de Bure Interferometre (PdBI) observations disclose several substructures of intense velocity-shear at scales as small as 6 milliparsec (mpc) (Falgarone et al 2009, hereafter FPH09).…”
Section: Introductionmentioning
confidence: 97%